Revision of DASHMM: Dynamic Adaptive System for Hierarchical Multipole Methods (Communications in Computational Physics, 2018)
We present version 1.2.0 of DASHMM, a general library implementing hierarchicalmultipole methods using the asynchronous multi-tasking HPX-5 runtimesystem. Compared with the previous release [10], this new version: (1) enables executionin both shared and distributed memory architectures; (2) extends DASHMM'sinfrastructure to support advanced multipole methods [18]; and (3) provides built-inimplementations of both the Yukawa [15] potential and Helmholtz [16] potential in thelow frequency regime. These additions have not impacted the user interface, whichremains simple and extensible.